1989
DOI: 10.1093/jac/24.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of efficacy and toxicity of aminoglycosides

Abstract: The relative efficacy of different aminoglycosides or of different dosage schedules of the same aminoglycoside should be quantitated and related to relative toxicity. Quantitative experimental indicators of efficacy should not only include MIC and MBC, but also the postantibiotic effect in vitro and in vivo, the emergence of resistance in in-vitro and in-vivo models, and the relationship between plasma concentration profiles and efficacy. Parameters of clinical efficacy are to be related to pharmacokinetic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
13

Year Published

1991
1991
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 24 publications
1
63
0
13
Order By: Relevance
“…Although we have recently shown that a 25 mg/kg loading dose of amikacin is necessary in patients with severe sepsis or septic shock in order to achieve therapeutic peak concentrations [3], aminoglycosides are potentially A c c e p t e d M a n u s c r i p t 5 nephrotoxic and clinical studies have suggested that renal impairment is more prevalent when there is pre-existing kidney dysfunction [12]. We therefore wondered whether optimising peak amikacin concentrations during CRRT with a higher dose regimen would be associated with prolonged high drug concentrations, which can potentially worsen renal function.…”
Section: Continuous Renal Replacement Therapy (Crrt) Is Increasingly mentioning
confidence: 99%
“…Although we have recently shown that a 25 mg/kg loading dose of amikacin is necessary in patients with severe sepsis or septic shock in order to achieve therapeutic peak concentrations [3], aminoglycosides are potentially A c c e p t e d M a n u s c r i p t 5 nephrotoxic and clinical studies have suggested that renal impairment is more prevalent when there is pre-existing kidney dysfunction [12]. We therefore wondered whether optimising peak amikacin concentrations during CRRT with a higher dose regimen would be associated with prolonged high drug concentrations, which can potentially worsen renal function.…”
Section: Continuous Renal Replacement Therapy (Crrt) Is Increasingly mentioning
confidence: 99%
“…Selectivity, rather than potency or affinity, is the most relevant feature that impacts on drug efficacy in vivo (Mattie et al, 1989;Troke et al, 1990;Brook, 1991;Vella and Floridia, 1998;Waldman, 2002). For example, despite its high TrkA binding affinity (K d , 10-100 pM), NGF has a narrow therapeutic window partly because of poor selectivity (e.g., it binds p75 receptors), partly because of pleiotropic activation, and partly because of a short half-life.…”
Section: Efficacy and Selectivitymentioning
confidence: 99%
“…However, data from in-vitro and experimental in-vivo studies suggest that once-daily dosing of aminoglycoside might be at least as efficacious and potentially less toxic (Frame et al, 1977;Blaser, Stone & Zinner, 1985a;Gerber et al, 1989;Mattie, Craig & Pechere, 1989). Single-daily dosing of aminoglycosides has also been studied clinically (Powell et al, 1983;Hollender et al, 1989).…”
Section: Introductionmentioning
confidence: 99%